Thomas Edison and the invention of the light bulb : separating fact from fiction - Peterson, Megan Cooley (Fact vs. fiction in U.S. history., 2023)
"Thomas Edison was a famous American inventor in the late 1800s. His work with light bulbs got a lot of attention. Over time, many stories were told about this work, including that he invented the light bulb. But this isn't true! Discover what's real and what's fiction through infographics, primary sources, and expertly leveled text"--